Mapping Potential Targets for Gold Mineralization: a Methodological Approach Based on Score Balances of Soil geochemical Data in the Amapari area, Amapá State, Brazil - Vieira Braga, Luis Paulo; Gerheim Porto, Claudio; Casado, João (Anuário do Instituto de Geociências, 2025)
Geochemical exploration in deeply weathered tropical terrains is often hampered by a strong modification of the primary geochemical signals on the surface, making it difficult to locate potential targets for gold mineralization relying on geochemical assays for Au in soil samples. This problem is particularly relevant in rain forest equatorial regions such as the Amapari area, Amapá state, Brazil, where the gold ore is hosted in a hydrothermally altered banded iron formation and where the prevailing humid tropical conditions contributed to developing regolith profiles that may be several tens of meters thick, topped by lateritic crusts or highly leached colluvial soils. In this study, we apply an innovative methodology based on score balances and data mining. The data set is composed of a vast soil geochemical survey conducted in the region. A training step based on mineralized and non-mineralized samples is essential to select the best variables to be adopted in a balanced formula whose score will be calculated over a validation area. The proposed method was successfully applied to highlight a mineralized trend in the Amapari region, which was not previously detected considering only Au grade or any other potential pathfinder metal alone. The method may be used in other regions and even for other valuable metals.